The coupling effect of water and fertilizer on the growth of tea plants [Camellia sinensis (L.) O. Kuntz]. (15th April 2016) - Wang, Yu; Fu, Delong; Pan, Lulu; Sun, Litao; Ding, Zhaotang
ABSTRACT: Water and fertilizer are the two main factors promoting the rapid growth of tea plants ( Camellia sinensis ). Using two-year-old rooted cutting of Wuniuzao ( Camellia sinensis ) as experimental materials, "311-B" D-saturation optimization design was carried out using 5, 4, and 4 levels of irrigation regimes, fertilizer nitrogen, and fertilizer phosphorus, with six replications. The raw date obtained was used of quadratic regression fitting for the plant height, new-tip length and dry matter weight. The coupling effects of these three factors [nitrogen (N0, water, and phosphorus (P)] on dry matter weight were significant. The effect order of single factor on dry matter weight was N>water>P, while the interactive effect order on the dry matter weight was N and water>P and water>N and P. An optimal combination with 0.485 g·pot −1 N, 0.274 g·pot −1 P, and once every 4-5 days of watering was proposed for the highest tea dry matter yield.